2020
DOI: 10.3390/app10051577
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Method to Test the Stability of High Bedding Rock Slop Subjected to Atomized Rain

Abstract: In the construction of high dams, many high rock slope failures occur due to flood discharge atomized rain. Based on the steel frame lifting technique and strength reduction materials, a comprehensive method is proposed in this paper to study the stability of high bedding rock slope subjected to atomized rain. The safety factor expression of the comprehensive method and the evaluation method for deformation instability were established according to the similarity theory of geomechanical model, failure criterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Due to complex geological process, there are numerous joints and weak interlayers (weak planes) inside the rock slope, which is very likely to induce the displacement of the slope along the weak layer under the action of blasting disturbance and thus further threatens slope stability [3][4][5]. The limit equilibrium analysis method (safety factor method) and the swallowtail mutation theory are advantageous methods for static analysis of slopes, of which the former is relatively mature in analyzing slope stability [6][7][8][9]. However, currently there is little research on the analysis of slope stability under the action of blasting disturbance by reasonably integrating relevant key parameter equations based on the swallowtail mutation theory.…”
Section: Introductionmentioning
confidence: 99%
“…Due to complex geological process, there are numerous joints and weak interlayers (weak planes) inside the rock slope, which is very likely to induce the displacement of the slope along the weak layer under the action of blasting disturbance and thus further threatens slope stability [3][4][5]. The limit equilibrium analysis method (safety factor method) and the swallowtail mutation theory are advantageous methods for static analysis of slopes, of which the former is relatively mature in analyzing slope stability [6][7][8][9]. However, currently there is little research on the analysis of slope stability under the action of blasting disturbance by reasonably integrating relevant key parameter equations based on the swallowtail mutation theory.…”
Section: Introductionmentioning
confidence: 99%
“…The damage of high bedding rock slopes by flood discharge of atomized rain was studied based on the slope in the Baihetan Hydropower Station. The results showed that the failure modes of the bedding rock slope were of two types: sliding-fracturing (the first slip block) and fracturing-sliding (other blocks) [18]. The long-term effects of rainfall recharge and the fluctuation of groundwater weaken the rock and soil, causing creep deformation and even landslides [19].…”
Section: Introductionmentioning
confidence: 99%